Osteoblast‐specific deficiency of ectonucleotide pyrophosphatase or phosphodiesterase‐1 engenders insulin resistance in high‐fat diet fed mice. Issue 6 (10th December 2020) - Roberts, Fiona L.; Rashdan, Nabil A.; Phadwal, Kanchan; Markby, Greg R.; Dillon, Scott; Zoll, Janna; Berger, Julian; Milne, Elspeth; Orriss, Isabel R.; Karsenty, Gerard; Le Saux, Olivier; Morton, Nicholas M.; et al.
Abstract: Supraphysiological levels of the osteoblast‐enriched mineralization regulator ectonucleotide pyrophosphatase or phosphodiesterase‐1 (NPP1) is associated with type 2 diabetes mellitus. We determined the impact of osteoblast‐specific Enpp1 ablation on skeletal structure and metabolic phenotype in mice. Female, but not male, 6‐week‐old mice lacking osteoblast NPP1 expression (osteoblast‐specific knockout [KO]) exhibited increased femoral bone volume or total volume (17.50% vs. 11.67%; p < .01), and reduced trabecular spacing (0.187 vs. 0.157 mm; p < .01) compared with floxed (control) mice. Furthermore, an enhanced ability of isolated osteoblasts from the osteoblast‐specific KO to calcify their matrix in vitro compared to fl/fl osteoblasts was observed ( p < .05). Male osteoblast‐specific KO and fl/fl mice showed comparable glucose and insulin tolerance despite increased levels of insulin–sensitizing under‐carboxylated osteocalcin (195% increase; p < .05). However, following high‐fat‐diet challenge, osteoblast‐specific KO mice showed impaired glucose and insulin tolerance compared with fl/fl mice. These data highlight a crucial local role for osteoblast NPP1 in skeletal development and a secondary metabolic impact that predominantly maintains insulin sensitivity. Abstract : Supraphysiological levels of the osteoblast‐enriched mineralization regulator ectonucleotide pyrophosphatase or phosphodiesterase‐1 (NPP1) is associated with type 2 diabetes mellitus. We have determined the impact of osteoblast‐specific Enpp1 ablation on skeletal structure and metabolic phenotype in mice. Our results highlight a crucial local role for osteoblast NPP1 in skeletal development and a secondary metabolic impact that predominantly maintains insulin sensitivity.